Emergency nurses’ disaster preparedness competencies: A focused mapping review and synthesis - Tshepo L. Motsepe; Shelley Schmollgruber (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Emergency nurses are at the front line of a health institution and are deemed competent to manage various situations, with disaster being one of them. Preparing for disaster is crucial as it will eliminate delays in providing care in conditions that would be abnormal in the daily running of an emergency department.